Stages and Developmental Tasks of Students and Their Implications in the Educational and Learning Process: An Islamic Psychopedagogical Perspective - Ummah, Khaira; Deliani, Nurfarida; Batubara, Juliana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The success of learning practices depends heavily on the extent to which educators understand the developmental characteristics of students at each age range. This study aims to analyze the stages of human development from childhood to adulthood, identify the competencies that need to be achieved at each stage, and explore their relevance to designing teaching and learning activities within an Islamic psychopedagogical framework. The method used is a literature review, which examines classical and contemporary developmental psychology literature and Islamic educational concepts. The findings indicate that early childhood requires a fun approach, elementary school children need concrete and collaborative experiences, adolescents need identity guidance and value reinforcement, and adults need meaningful and contextual learning. The Islamic perspective emphasizes that students have an innate nature that must be developed holistically, not limited to intellectual aspects alone. This study also identifies current issues such as promiscuity and early marriage as indications of failure to achieve developmental tasks that require values-based educational solutions. In conclusion, aligning learning strategies with developmental stages is key to achieving the goal of holistic education that prepares quality individuals in all dimensions of their lives.